Alkaline peptone water plus 0.5% agar suitable for transport of Vibrio cholerae - Meiyanti, Meiyanti; Salim, Oktavianus Ch.; Surjawidjaja, Julius E.; Lesmana, Murad (Universa Medicina, 2011)
Microbiological procedures for V. cholerae isolation from clinical specimens are important factors in clinical and epidemiological management of cholera. The standard preservation medium for enteric pathogenic bacteria, including V. cholerae, is Cary-Blair medium (CB), a semisolid medium for preservation and transport of specimens containing intestinal bacteria. A special medium for Vibrio organisms is alkaline peptone water (APW), which is both a transport and an enrichment medium. The purpose of this study was to ascertain the suitability of APW supplemented with 0.5% agar (APW-0.5) as a sensititive preservation-transport medium for rectal swab specimens for isolation of V. cholerae. A total of 144 paired rectal swab specimens were collected from children and adults with acute diarrhea. Of each specimen pair, one was placed in CB and the other in APW-0.5, from which they were plated out to thiosulfate citrate bile sucrose (TCBS) agar. Altogether, from both CB and APW-0.5 transported specimens, V. cholerae non-O1 was present in 29 (20.1%) specimens, while only 2 (1.4%) specimens were positive in CB and 9 (6.3%) positive in APW-0.5 transported specimens. The number of V. cholerae non-O1 isolates from APW-0.5 transported specimens was significantly higher (p=0.000) as compared to that from Cary-Blair transported specimens. It may be concluded that for isolation of V. cholerae, specimen transport in APW-0.5 medium was more effective than transport in Cary-Blair medium.